Minimizing Drug Adverse Events by Informing About the Nocebo Effect—An Experimental Study - Pan, Yiqi; Kinitz, Timm; Stapic, Marin; Nestoriuc, Yvonne (Frontiers in Psychiatry, 2019)
Relevance. Informing patients about potential adverse events as part of the informed consent may facilitate the development of nocebo-driven drug adverse events (nocebo side effects). Objective. To investigate whether informing about the nocebo effect using a short information sheet can reduce nocebo side effects. Methods. A total of N = 44 participants with weekly headaches for at least 6 months were recruited by using the cover story of a clinical trial for a headache medication. In reality, all participants took a placebo pill and were randomized to the nocebo information group or the standard leaflet group. Participants were instructed to read the bogus medication leaflet entailing side effects information shortly before pill intake. The nocebo group additionally received an explanation about the nocebo effect as part of the leaflet. Questionnaires were completed at baseline, 2 minutes, and 4 days after the pill intake. We conducted general linear models with bootstrap sampling. Baseline symptoms were included as a covariate. Results. Most participants (70.5%) reported nocebo side effects at 2 minutes. Participants who received the nocebo information (n = 24) reported less nocebo symptoms than the control group (n = 20) (estimated difference: 3.3, BCa 95% CI [1.14; 5.15], p = .01, Cohen’s d = 0.59). Baseline symptoms, perceived sensitivity to medicine, and side effect expectations each moderated the group effect (estimated difference in slope: 0.47, BCa 95% CI [0.19; 0.73], p = .001, d = 0.75; 1.07 [0.27; 1.61], p = .006, d = 0.73; 1.57 [0.38; 2.76], p = .02, d = 0.58). No group differences were found at 4-day follow-up. After revealing the actual aim of the study, 86% of the participants evaluated the nocebo information to be helpful in general. Conclusions. Results provide the first evidence that informing about the nocebo effect can reduce nocebo side effects.